2010
DOI: 10.1128/jvi.00422-10
|View full text |Cite
|
Sign up to set email alerts
|

Role for Complement in the Development of Seizures following Acute Viral Infection

Abstract: Complement, part of the innate immune system, acts to remove pathogens and unwanted host material. Complement is known to function in all tissues, including the central nervous system (CNS). In this study, we demonstrated the importance of the complement system within the CNS in the development of behavioral seizures following Theiler's murine encephalomyelitis virus (TMEV) infection. C57BL/6 mice, deficient in complement component C3, developed significantly fewer behavioral seizures following TMEV infection,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
46
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 47 publications
(70 reference statements)
1
46
0
1
Order By: Relevance
“…Complement activation in the CNS is increasingly recognised to be associated with exacerbation and progression of tissue injury in degenerative and inflammatory diseases [21,22]. Dysregulation of the complement system in epilepsy has been observed both in human and animal studies [23][24][25][26][27]. For example, sequential infusion of individual proteins of the membrane attack pathway (C5b6, C7, C8, and C9) into the hippocampus of awake, freely moving rats induced both behavioural and electrographic seizures as well as neurotoxicity, suggesting a direct role for the complement system in epileptogenesis [28].…”
Section: Introductionmentioning
confidence: 99%
“…Complement activation in the CNS is increasingly recognised to be associated with exacerbation and progression of tissue injury in degenerative and inflammatory diseases [21,22]. Dysregulation of the complement system in epilepsy has been observed both in human and animal studies [23][24][25][26][27]. For example, sequential infusion of individual proteins of the membrane attack pathway (C5b6, C7, C8, and C9) into the hippocampus of awake, freely moving rats induced both behavioural and electrographic seizures as well as neurotoxicity, suggesting a direct role for the complement system in epileptogenesis [28].…”
Section: Introductionmentioning
confidence: 99%
“…We previously found that tumor necrosis factor alpha (TNF-␣) and interleukin-6 (IL-6) and concomitant inflammatory changes in the brain contribute to the development of acute seizures (5,7). Further, we have shown the importance of complement component 3 (C3) activation in the central nervous system (CNS) for the development of acute seizures (9). C3 activation within the brain in response to viral infection may help drive inflammation and cytokine production, ultimately leading to seizures.…”
mentioning
confidence: 99%
“…Our earlier studies concentrated on innate immune contributions to the development of seizures (5,7,9). We previously found that tumor necrosis factor alpha (TNF-␣) and interleukin-6 (IL-6) and concomitant inflammatory changes in the brain contribute to the development of acute seizures (5,7).…”
mentioning
confidence: 99%
“…Our recent work demonstrated an important role for microglia and macrophages in acute seizures (15,16,19). PCR arrays and antibody depletion studies were used to determine that monocyte-derived cells were important in the development of acute seizures (16).…”
mentioning
confidence: 99%